Evaluation of a high-resolution micro-sized magic angle spinning (HRμMAS) probe for NMR-based metabolomic studies of nanoliter samples. Issue 37 (6th September 2016) - Duong, Nghia Tuan; Endo, Yuki; Nemoto, Takahiro; Kato, Hiroshi; Bouzier-Sore, Anne-Karine; Nishiyama, Yusuke; Wong, Alan
Abstract : This study reports the performance of a 1 mm HRμMAS NMR micro-probe for metabolomic studies. Abstract : This study evaluates the performances of a recently introduced 1 mm HRμMAS NMR probe for metabolic profiling of nanoliter samples. It examines essential NMR criteria such as spectral data qualities and repeatability, and experimental practicality. The report also discusses the difficulties related to the sample preparation in HRμMAS experiments and considers possible solutions and improvements.